ENVIRONMENTAL ASPECTS OF THE TRANSPORT SYSTEM OF CITIES OF THE RUSSIAN FEDERATION (Вестник университета)
The relevance, solutions and other issues on the aspects and increase the efficiency of the transport system of cities of the Russian Federation are discussed. The ways to preserve the environment from various toxic substances that daily penetrate the atmosphere from the use of different types of transport are proposed. The development of the environmental protection system throughout the country, compliance with standards of toxic emissions will ensure the creation of a healthy environment, increase life expectancy and quality of life.